Space Law, Shariʿa, and the Legal Place of a Scientific Enterprise: The Case for a Parallel Challenge of Sovereignty. (18th March 2016) - Durrani, Haris
Abstract : This article synthesizes questions of sovereignty in shariʿa scholarship today with parallel challenges in the nascent field of space law. Space law's focus on regulating political, economic, and social factors related to outer space particularly its focus on the "peaceful uses of outer space" against its prevalent military applications— makes space law especially relevant to the "Muslim world, " where Euroamerican dominance of this military high ground represents a specific differential of violence, power, and authority. Using a comparative approach to bring together these two perceived ends of law in their social, political, technological, and religious interactions with modern legal structures, this paper investigates the nature of law and its relationship to sovereignty and the state through differentials of power. Focusing on each field's debated notions of "law" as opposed to "governance, " the veracity and multiplicity of shared or parallel legal contentions illustrate the challenge (for some, the crisis) of modernity as a legal (and broader) project of differentials of power across legal scopes. This shows that further comparative interrogations of space law and shariʿa can continue to produce, and perhaps resolve, similar and pressing questions about the problem of sovereignty in modernity.